1994
DOI: 10.1111/j.1476-5381.1994.tb17112.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase (NEP) inhibition in rats with established pulmonary hypertension secondary to chronic hypoxia

Abstract: 1Atrial natriuretic peptide (ANP) causes vasorelaxation in the pulmonary vasculature. ANP levels are elevated in conditions characterized by pulmonary hypertension and it has been hypothesized that ANP may be autoregulatory in the pulmonary circulation. 2 One route of ANP metabolism in vivo is by the action of the enzyme neutral endopeptidase (NEP). We have studied the effects of the NEP inhibitor, SCH 42495, in rats with established pulmonary hypertension secondary to chronic hypoxia. 3 Rats (n = 32) were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…ClinicalTrials.gov identifier: NCT03229499). Furthermore, the effect of oestrogen inhibition with tamoxifen will be investigated in patients with PAH in a small randomised controlled trial (RCT; (Dempsey et al, 2009), pharmacological inhibition of neprilysin alone or in combination with PDE5 inhibition attenuated PH in chronic hypoxic rats without affecting systemic circulation (Baliga et al, 2008;Thompson, Sheedy, & Morice, 1994).…”
Section: Current Treatment Options In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…ClinicalTrials.gov identifier: NCT03229499). Furthermore, the effect of oestrogen inhibition with tamoxifen will be investigated in patients with PAH in a small randomised controlled trial (RCT; (Dempsey et al, 2009), pharmacological inhibition of neprilysin alone or in combination with PDE5 inhibition attenuated PH in chronic hypoxic rats without affecting systemic circulation (Baliga et al, 2008;Thompson, Sheedy, & Morice, 1994).…”
Section: Current Treatment Options In Pahmentioning
confidence: 99%
“…Studies of neprilysin in animal models of PH showed conflicting results. While neprilysin‐deficient mice exhibited an exaggerated response to chronic hypoxia (Dempsey et al, 2009), pharmacological inhibition of neprilysin alone or in combination with PDE5 inhibition attenuated PH in chronic hypoxic rats without affecting systemic circulation (Baliga et al, 2008; Thompson, Sheedy, & Morice, 1994). Recently, the efficacy and safety of the neprilysin inhibitor racecadotril was tested in an RCT in PAH.…”
Section: Novel Treatment Options Targeting Specific Pathways In Pahmentioning
confidence: 99%
“…NEPs appear to have an underlying role in the pathogenesis of PH ( Dempsey et al, 2009 ). NEP inhibitors have produced promising results in models of PH, both as monotherapy ( Klinger et al, 1993 ; Thompson et al, 2012 ) or in combination with PDE5 inhibition ( Baliga et al, 2008 ). This is largely due to their ability to increase circulating atrial natriuretic peptide.…”
Section: What Is Not Known? Future Prospects For Neuropeptides As a Tmentioning
confidence: 99%
“…NEP is a membrane bound zinc metallopeptidase responsible for the metabolism and inactivation of an array of vasodilator (e.g., natriuretic peptides, adrenomedullin, vasoactive intestinal peptide) and vasoconstrictor (e.g., angiotensin II, endothelin-1 [ET-1]) peptides (Erdos & Skidgel, 1989;Kenny & Stephenson, 1988). Indeed, preclinical evidence indicates that NEP −/− mice are less susceptible to hypoxiainduced pulmonary oedema (Irwin, Patot, Tucker, & Bowen, 2005) and that inhibition of NEP attenuates hypoxia-induced PH by potentiating the action of natriuretic peptides Thompson, Sheedy, & Morice, 1994;Winter, Zhao, Krausz, & Hughes, 1991). These observations fit with the up-regulation of NEP in the pulmonary circulation during acute lung injury and heart failure (Abassi, Kotob, Golomb, Pieruzzi, & Keiser, 1995;Hashimoto, Amaya, Oh-Hashi, Kiuchi, & Hashimoto, 2010).…”
Section: Introductionmentioning
confidence: 99%